Assessment of the Macroeconomic Risk Analysis of International Credit Rating Agencies against the Principles of Soundness and Credibility - Simon, József; Simon-András, Henrietta (Public Finance Quarterly, 2019)
International credit rating agencies regularly (twice a year) assess the risk level of sovereign debt, and thus that of a given country. In order to identify risks, each credit rating agency has developed its own methodology to assess economic and public finance processes and identify the emerging risks. The evaluations carried out influence at the international level the financing possibilities of a given country and its conditions. The improving result of evaluations by international credit rating agencies has become one of the requirements for the success of economic policy. However, this can only be a realistic condition and a measure of success if the evaluation made is methodologically sound and the evaluations resulting from their consistent implementation are scientifically credible. This article describes in detail the evaluation methodology applied by the three major international credit rating agencies to evaluate the individual countries and sovereign debt. After presenting the general aspects, the article draws attention to the fact that the principles of objectivity, authenticity and methodological determination are enforced in practice in the evaluations of international credit rating agencies to a limited extent.